Reference Interval for Glycated Albumin, 1,5-AG/GA, and GA/HbA1c Ratios and Cut-Off Values for Type 1, Type 2, and Gestational Diabetes: A Cross-Sectional Study - Yusra Al-Lahham; Waldemar Volanski; Liana Signorini; Ademir Luiz do Prado; Glaucio Valdameri; Vivian Rotuno Moure; Marciane Welter; Alexessander C. Alves; Marcel Henrique Marcondes Sari; Fabiane Gomes de Moraes Rego; Geraldo Picheth (Biomedicines, 2024)
Background/Objectives: Glycated albumin (GA) serves as a biomarker for short-term glycemic control (2–3 weeks), playing a role in diabetes management. Our goal was to establish reference intervals (RIs) for serum GA, and the ratios of 1,5-anhydroglucitol to GA (AGI) and GA to HbA1c in a Euro-Brazilian pediatric population (10 y, n = 299), adults (43.5 y; n = 290), and pregnant women (26 y, n = 406; 26.5 ± 3.1 gestation weeks). Methods: Receiver operating characteristic curve analysis was employed to determine RIs for type 1 diabetes (T1D) in children (n = 148) and adults (n = 81), type 2 diabetes (T2D, n = 283), and gestational diabetes mellitus (GDM, n = 177). Results: Both non-pregnant and pregnant women exhibited GA RIs of 10.0–13.3% and 10.6–14.7%, respectively. The AGI ratio varied from 1.2–4.3 in children, 0.9–3.6 in adults, and 0.8–3.1 in pregnant women. Meanwhile, the GA/HbA1c ratio ranged from 1.8–2.6 in children and adults to 2.3–3.6 in pregnant women. GA and AGI ratios accurately differentiated between T1D and T2D, demonstrating high sensitivity (>84%) and specificity (>97%), with AGI showing superior performance (AUC > 0.99). The GA/HbA1c ratio exhibited moderate discriminatory power (AUC > 0.733) but was less effective in distinguishing adult-onset T1D and T2D, suggesting its limited utility in certain groups. Conclusions: The proposed RIs are consistent with those of other Caucasian populations, affirming their relevance for Euro-Brazilian patients. The GA and AGI ratios emerge as valuable diagnostic tools for T1D and T2D, though their reduced sensitivity in diagnosing GDM warrants further investigation. Clinicians might leverage GA and AGI ratios for more tailored diabetes management, especially when HbA1c results are not optimal.